Clinical characteristics of anti-myelin oligodendrocyte glycoprotein antibody among aquaporin-4 negative neuromyelitis optica spectrum disorders in Egyptian patients - Sara I. Taha; Salwa I. Bakr; Nermeen T. Fouad; Dina Zamzam; Yasmine A. Mohamed (Scientific Reports)
Abstract Some patients with neuromyelitis optica spectrum disorder (NMOSD)-like symptoms test negative for anti-aquaporin-4 (anti-AQP4) antibodies. Among them, a subset has antibodies targeting myelin oligodendrocyte glycoprotein (MOG), a condition now termed MOG antibody-associated disease (MOGAD). MOGAD shares features with NMOSD, like optic neuritis and myelitis, but differs in pathophysiology, clinical presentation, imaging findings, and biomarkers. The present study investigated the prevalence of anti-myelin oligodendrocyte glycoprotein (anti-MOG) antibodies in anti-AQP4 seronegative Egyptian patients initially diagnosed with NMOSD and the link between their presence and clinical characteristics and disease-induced disability to gain insights into MOGAD. This pilot cross-sectional study included 40 anti-AQP4 antibody-negative patients initially diagnosed with NMOSD, six children and 34 adults. They were screened for anti-MOG antibodies by the indirect immunofluorescence cell-based assay. Of all included patients, only 7.5% (n = 3) were positive for anti-MOG antibodies and had significantly higher disability scores than seronegative patients (p = 0.021). The presence of anti-MOG antibodies was not significantly associated with age (p = 0.696), gender (p = 0.232), type of relapse (p = 0.488), number of attacks (p = 0.968), family history of consanguinity (p = 0.211), family history of autoimmune disease (p = 0.608), nor with smoking (p = 0.608). Detecting anti-MOG antibodies in anti-AQP4-negative NMOSD patients is essential for accurate diagnosis and personalized treatment, as MOGAD is now recognized as a separate clinical entity.